An experimental investigation concerning the effect of AFP defects on progressive damage in CFRP coupons. (1st January 2022) - Anay, Rafal; Miller, Dennis; Tssema, Addis; Wehbe, Roudy; Ziehl, Paul; Tatting, Brian; Gurdal, Zafer; Harik, Ramy; Kidane, Addis
Abstract: Manufacturing of composite laminates using the fiber placement process introduces the possibility of several types of defects and features that are not present in traditional hand-layup fabrication techniques. The effect of these defects on structural performance and failure has not been fully investigated, especially for those defects with small geometrical features. The innovation lies in using advanced methods to capture the effect of defects generated during manufacturing processes which can be used to determine if these defects warrant immediate repair to ensure part integrity. Several types and configurations of defects that may occur during the automated fiber placement (AFP) process were inserted within the coupons. Acoustic emission (AE) was employed as a nondestructive evaluation technique to investigate correlations between mechanical properties and damage propagation during tension and 3-point bending tests. Digital Image Correlation (DIC) was utilized to monitor damage progression in the bending test.